A selective histone deacetylase-6 inhibitor improves BDNF trafficking in hippocampal neurons from Mecp2 knockout mice: implications for Rett syndrome - Xu, Xin; Kozikowski, Alan; Pozzo-Miller, Lucas (Frontiers in Cellular Neuroscience, 2014)
Rett syndrome (RTT) is a neurodevelopmental disorder caused by loss-of-function mutations in the transcriptional modulator methyl-CpG-binding protein 2 (MECP2). One of the most prominent gene targets of MeCP2 is brain-derived neurotrophic factor (Bdnf), a potent modulator of activity-dependent synaptic development, function and plasticity. Dysfunctional BDNF signaling has been demonstrated in several pathophysiological mechanisms of RTT disease progression. To evaluate whether the dynamics of BDNF trafficking is affected by Mecp2 deletion, we analyzed movements of BDNF tagged with yellow fluorescent protein (YFP) in cultured hippocampal neurons by time-lapse fluorescence imaging. We found that both anterograde and retrograde vesicular trafficking of BDNF-YFP are significantly impaired in Mecp2 knockout hippocampal neurons. Selective inhibitors of histone deacetylase 6 (HDAC6) show neuroprotective effects in neurodegenerative diseases and stimulate microtubule-dependent vesicular trafficking of BDNF-containing dense core vesicles. Here, we show that the selective HDAC6 inhibitor Tubastatin-A increased the velocity of BDNF-YFP vesicles in Mecp2 knockout neurons in both directions by increasing αtubulin acetylation. Tubastatin-A also restored activity-dependent BDNF release from Mecp2 knockout neurons to levels comparable to those shown by wildtype neurons. These findings demonstrate that a selective HDAC6 inhibitor is a potential pharmacological strategy to reverse cellular and synaptic impairments in RTT resulting from impaired BDNF signaling.